Advertising and promotion - Hackley, Chris; Hackley, Rungpaka Amy (London SAGE Publications, 2018)
"Offering a short, concise and creative take on advertising and promotion, the new edition includes more on digital and social media marketing while using a wider range of visual examples and case studies"--Provided by publisher.
Keywords: Advertising; Advertising -- Social aspects; Sales promotion; Advertising -- Brand name products